Association between psychological distress and mental help-seeking intentions in international students of national university of Singapore: a mediation analysis of mental health literacy - Fanmin Zeng; Wong Chee Meng John; Dan Qiao; Xueli Sun (BMC Public Health, 2023)
Abstract Background International students encounter a wide range of challenges that can have a significant impact on their mental health. Seeking help is one of the primary means of managing mental health, and more attention is required. This study aimed to investigate the psychological distress(PD), mental health literacy(MHL), and mental help-seeking intentions(MHSI) in international students of National University of Singapore(NUS), to explore the correlation between the three and to verify the mediating role of MHL in PD and MHSI. Methods This cross-sectional study was conducted between May and July 2023 using the Mental Help Seeking Intention Scale(MHSIS), Patient Health Questionnaire-9(PHQ-9), Generalized Anxiety Disorder-7(GAD-7), and Mental Health Literacy Scale(MHLS). 281 international students(177 males, 104 females;) in NUS completed self-report questionnaires. SPSS 25.0 was applied to the data for descriptive analysis, Pearson correlation analysis and stepwise regression analysis. Mediation analysis fully for all potential confounding factors were conducted. Results Significant correlations were found between PD, MHL and MHSI. MHLS- knowledge of how to seek professional information(MHLS- H) completely mediated the association of anxiety with MHSI[B=-0.271; 95% confidence interval(CI): (-0.067, 0.0037)]; MHLS- attitude that promote recognition or appropriate help-seeking behavior(stigma)(MHLS- H) partially mediated the association of PD with MHSI[B = 0.104, 95% CI: (0.008, 0.179)]; with mediating effects accounting for 100% and 24.847% of the total effect. In addition, demographic variables such as gender, years in Singapore and residence type mediated both the direct and indirect effect of the mediation model. Conclusions MHL mediated both the direct and indirect effects on the association between PD and MHSI, especially, the mediator of the MHLS- H and MHL-A. It means that MHSI in this population can be improved by increasing MHL and thus the PD. The findings suggest that, such as providing information about how to access to professional services and promoting disorder recognition to the international students, may help them develop their psychological well-being and good mental health care decisions.